Efektivitas Penyerapan Zat Besi dari Buah Naga dan Pepaya terhadap Kadar Hemoglobin Ibu Hamil di Puskesmas Sukarejo, Tanjung Jabung Barat - Danaz Nst, Atika Fadhilah; Herawati, Netti; Amanda, Suci (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Anemia is the most common nutritional problem and its risk increases in pregnancy and is associated with inadequate iron intake. The prevalence of anemic pregnant women is still quite high, especially in developing countries. Aimed to analyze the effectiveness of Fe absorption from dragon fruit and papaya on the increase in Hb levels of pregnant women who take Fe tablets. This study was a quasy experimental with a two group pre-post test design conducted on 48 pregnant women registered at the Sukarejo Health Center, Tanjung Jabung Barat. Participants were divided into the Dragon fruit intervention group of 24 mothers, and the other 24 were included in the Papaya fruit group. The analysis showed a significant difference in Hb levels in the pre and post test Dragon fruit group with a value of p=0.000, as well as in the Papaya fruit group with a value of p=0.042. Giving dragon fruit is more effective than giving papaya fruit to increase the Hb level of pregnant women who consume Fe tablets.